2020
DOI: 10.1063/5.0009396
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Doppler shift upon reflection from a right angle prism

Abstract: This Letter reports the observation of a rotational Doppler shift on reflected beams carrying Orbital Angular Momentum (OAM). More precisely, we study the beat frequency of two optical beams carrying OAM with opposite signs, reflected on a right angle prism. We show that the interference of the two beams leads to a daisy-like pattern that rotates at twice the rotating frequency of the prism. The rotational Doppler frequency shift is equal to the OAM topological charge change times the rotational frequency. Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Second, and most of all, just as the linear momentum of the wave has to change during wave and object interaction in the case of the linear Doppler effect, the total angular momentum (SAM+OAM) of the wave has also to change during wave and rotating body interaction [2,3] for the rotational Doppler effect. In optics, its implementation has thus been restricted either i) to the transmission through specific rotating elements such as spiral wave plates or dove prisms [4,5], or ii) to the scattering by rough surfaces [6][7][8] or from ion-acoustic vortices in laser plasma [9], or iii) to the reflection on phase cona emile@univ-rennes1.fr jugated mirrors [10,11], metasurfaces and helicoidal reflectors [12][13][14] or prisms [15].…”
Section: Introductionmentioning
confidence: 99%
“…Second, and most of all, just as the linear momentum of the wave has to change during wave and object interaction in the case of the linear Doppler effect, the total angular momentum (SAM+OAM) of the wave has also to change during wave and rotating body interaction [2,3] for the rotational Doppler effect. In optics, its implementation has thus been restricted either i) to the transmission through specific rotating elements such as spiral wave plates or dove prisms [4,5], or ii) to the scattering by rough surfaces [6][7][8] or from ion-acoustic vortices in laser plasma [9], or iii) to the reflection on phase cona emile@univ-rennes1.fr jugated mirrors [10,11], metasurfaces and helicoidal reflectors [12][13][14] or prisms [15].…”
Section: Introductionmentioning
confidence: 99%
“…Conceptually, the experiment performed here is very different from most of the experiments proposed or realized on rotational Doppler effect in reflection, up to now. Most of the time, an OAM beam is shined on a surface that changes the topological charge of the beam [8][9][10][11]14]. This also includes dedicated metasurfaces [12] that changes the angular momentum (spin, OAM or both) of the incoming beam.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, during interaction with the rotating body, the total angular momentum of the electromagnetic field has to change [7]. Therefore, in reflection, the rotational Doppler effect has been limited to the scattering by rough surfaces [8][9][10], or to the reflection on phase conjugated mirrors [11], metasurfaces and helicoidal reflectors [12,13] or prisms [14]. Very recently, it has been shown that a rotational Doppler shift can be isolated in the decomposition of the image of an object having a rotational symmetry in a bistatic configuration [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Fabrizio et al [13] made an observation of twisted light in rotating blackhole. Due to the rotational Doppler effect [14][15][16], it is advantageous in remote sensing, image restoration, superresolution imaging, metrology, and so on [17][18][19][20][21][22][23]. Researchers found that due to the low diffraction limit, the vortex beam could replace the trivial Gaussian beam to improve the resolution of imaging, e.g., stimulated emission depletion, which can be of great use to biological and clinical medicine research [24].…”
Section: Introductionmentioning
confidence: 99%